"Times of war and time of uncertain peace": Narratives of parents of childhood cancer survivors - Rhyquelle Rhibna Neris; Ana Carolina Andrade Biaggi Leite; Elizabeth Papathanassoglou; Cristina Garcia-Vivar; Juliana de Souza; Lucila Castanheira Nascimento (Universidade de São Paulo, 2024)
Abstract Objective: to analyze the meaning attributed by parents to the extended and permanent survival of childhood cancer. Method: qualitative narrative inquiry, developed with parents of adolescents and young adults who survived childhood cancer. Recruitment and data collection involved virtual and in-person approaches. The data were collected through semi-structured interviews. Data were analyzed according to reflective thematic analysis. Results: a total of ten parents were included in the study. Two thematic narrative syntheses were constructed: "Times of war"; and "Time of uncertain peace", with their respective sub-themes. The cancer diagnosis marks the beginning of times of war in the parents' lives. They experience cancer treatment as "highs and lows" with potential threats to their children's lives. After that, "Time of uncertain peace" are reached, and the balance of the family unit is reestablished. However, the fear of recurrence makes the family peace uncertain, and its maintenance requires constant vigilance and attention to the signs and symptoms of a possible new battle. Conclusion: the results highlight the experience of being a parent of a childhood cancer survivor and can be applied to develop models of care centered on the survivors' family.